The Roles of Escorts for Women Who Are Having Cases Before the Law in Courts Under the Legal Jurisdiction of Palembang City - Vera Novianti; Lusi Apriyani (Universitas Sriwijaya, 2023)
Chapter 1 article 1 of the Regulation of the Supreme Court of the Republic of Indonesia number 3 of 2017 has clearly defined that women having cases before the law consist of women who violate the law, women who testify in court, female crime victims, and women who stands as a party in a case. They have the right to get protection, access to justice, and receive fair treatment without discrimination. In addition, they are also entitled to receive recovery and restitution from the damage caused by a crime. Protection during the judicial process must also be provided because of the potential threats they may face in cases involving them. Therefore, it is very important to provide trustworthy escorts while they are following the judicial process so that their rights can be fulfilled and properly accommodated.